2017
DOI: 10.1016/j.jacr.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A Mentorship and Networking Group for Women in Radiology

Abstract: THE PROBLEM: TOO FEW FEMALE ROLE MODELS IN RADIOLOGYWomen are underrepresented in radiology [1]. A 2014 study found that the percentages of female practicing radiologists (23.5%), academic radiology faculty (26.1%), radiology residents (27.8%), and radiology applicants (28.1%) were all substantially below the percentage of women graduating from medical school in the United States (48.3%) [2]. Additionally, of the twenty largest residency training programs in the US, radiology ranked ninth for overall size but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…After screening titles and abstracts, we reviewed 146 papers. A final 24 primary publications were identified for the review as well as eight review articles 13 15 22-27 : we found 20 primary observational studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] which were either crosssectional or before-and-after studies with no study using interrupted time series or similar analysis, and we identified four randomised controlled trials (RCTs). [48][49][50][51] We also identified 19 publications discussing mentoring in relation to gender but not meeting our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…After screening titles and abstracts, we reviewed 146 papers. A final 24 primary publications were identified for the review as well as eight review articles 13 15 22-27 : we found 20 primary observational studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] which were either crosssectional or before-and-after studies with no study using interrupted time series or similar analysis, and we identified four randomised controlled trials (RCTs). [48][49][50][51] We also identified 19 publications discussing mentoring in relation to gender but not meeting our eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Last, medical schools and residency programs certainly play a crucial role in closing the gender gap. Since several studies addressed the importance of mentoring in choosing a career in radiology and one even highlighted the significant impact of role models on women, we call for mentoring programs such as the one at the Massachusetts General Hospital [134] and the Women in Radiology Group at Indiana University [135].…”
Section: Discussionmentioning
confidence: 99%
“…One strategy already being practiced widely involves working with local radiology student interest groups to cosponsor career panel discussions, often featuring enthusiastic radiologists and trainees. Another important forum that is increasingly popular is the "women in radiology" career event, which features panels of female trainees, faculty, and local alumni working in a variety of practice settings [10]. Programs should also participate fully in their schools' local residency fairs and specialty speed round events, both designed to expose students to the various medical specialties.…”
Section: Controlling Our Own Narrativementioning
confidence: 99%